Anxiolytic Effect of Chronic Administration of Gallic acid in Rats - Priyanka Singh, Rahul MK, Vijay Thawani, Pemminati Sudhakar (Journal of Applied Pharmaceutical Science, 2013)
Anxiety is a cardinal symptom of many psychiatric disorders and an inevitable component of many medical and surgical conditions. It is a universal human emotion, closely allied with appropriate fear presumably serving psycho biologically adaptive purposes. Anxiety is a normal emotional behaviour. When it is severe and/or chronic, it becomes pathological and can precipitate or aggravate cardiovascular and psychiatric disorders. Although many drugs are available in allopathic medicine to treat anxiety disorders, they produce various systemic side effects. Gallic acid has been identified as active ingredient found in gall nuts, sumac, witch hazel, tea leaves and oak bark. In the present study, we have attempted to evaluate the anti-anxiety- activity of Gallic acid in rats by employing, elevated plus maze and bright and dark arena. The rats were divided into five groups, each group containing six animals. The effects of the test drug Gallic acid (at 0.05, 0.1 and 0.2 mg/kg doses),the standard anxiolytic, diazepam (1.0 mg/kg) and control group 14% Dimethyl sulfoxide(10ml/kg) were assessed after repeated doses administration for ten days. The results suggest that, Gallic acid exhibited anxiolytic like activity comparable to diazepam.
Keywords: Anxiolytic, Gallic acid, Diazepam, Rats.